Le marche mondial des produits laitiers - Tendances economiques. Produits laitiers - International Livestock Centre for Africa (1979)
Data on dairy product exporting and importing areas, and EEC stocks of butter & skim milk powder w. ref. to price trends, trade volume and market prospects.